2009
DOI: 10.1080/10715760903137002
|View full text |Cite
|
Sign up to set email alerts
|

A class of imidazolium salts is anti-oxidative and anti-fibrotic in hepatic stellate cells

Abstract: A class of imidazolium salts (IMSs) is routinely used in organic synthetic chemistry as precursors to generate N-heterocyclic carbenes (NHCs) with catalytic activity. However, their biological properties are largely unknown. The current study investigates the biological activity of a typical NHC precursor DBZIM and its trimer TDBZIM in hepatic stellate cells (HSCs), which is an in vitro model for studying liver fibrosis. The results show that HSCs treated with IMSs have an enhanced GSH/GSSG ratio and a reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…10 Here, we confirmed that DPIM at much lower concentrations (50, 100, and 200 mM) for 48 h also dose dependently suppressed the expression of the fibrogenic Col1a1 gene, but not the a-SMA (Figures 1b-d Supplementary Figure 2a). However, DPIM treatment (10, 100, 200 mM for 48 h) failed to significantly inhibit the proliferation of HSC-T6 cells (Supplementary Figure 2b), albeit a slight decrease in proliferation was achieved at 200 mM (P ¼ 0.08, compared with 0 mM).…”
Section: Effects Of Dpim In Hsc-t6 Cellssupporting
confidence: 72%
See 4 more Smart Citations
“…10 Here, we confirmed that DPIM at much lower concentrations (50, 100, and 200 mM) for 48 h also dose dependently suppressed the expression of the fibrogenic Col1a1 gene, but not the a-SMA (Figures 1b-d Supplementary Figure 2a). However, DPIM treatment (10, 100, 200 mM for 48 h) failed to significantly inhibit the proliferation of HSC-T6 cells (Supplementary Figure 2b), albeit a slight decrease in proliferation was achieved at 200 mM (P ¼ 0.08, compared with 0 mM).…”
Section: Effects Of Dpim In Hsc-t6 Cellssupporting
confidence: 72%
“…10 Primary antibodies used for the western blots were a-SMA (1:1000 dilution, Sigma), a-Tubulin (1:2000 dilution, Santa Cruz Biotech, USA), TIMP-1 (1:500 dilution, sc-80363, Santa Cruz Biotech), MCP-1 (1:500 dilution, sc-28879, Santa Cruz Biotech).…”
Section: Protein Extraction Sds-page and Immunoblotmentioning
confidence: 99%
See 3 more Smart Citations